PENGARUH APLIKASI BIOGEOTEKSTIL DAN PROBIOTIK TERHADAP RESPIRASI TANAH DAN BIOMASSA MIKROBA DALAM BUDIDAYA KENTANG DI ANDISOL - Fajriyah, Azizatul; Utami, Sri Rahayu; Maulidiyah, Nurul; Permatasari, Wulan; Yu-Min, Wang; Suprayogo, Didik (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2025)
Soil respiration and microbial biomass are key biological indicators for soil fertility, especially in the context of agricultural sustainability. Potatoes (Solanum tuberosum L.) are a high-demand crop; their cropping system often ignores conservation principles, causing land degradation. Applying biogeotextiles and probiotics might be potential solution to reduce erosion and maintain soil fertility. This study aimed to evaluate the impact of biogeotextile and probiotic applications on soil respiration and microbial biomass as indicators of soil health in potato farming in Andisols. Randomized Block Design Factorial was used with biogeotextile application as the first factor and and probiotic as the second factor. Four treatments were applied, i.e., control (no treatment), biogeotextile, probiotic, and a combination of biogeotextile and probiotic. Soil pH, % organic C, % N-total, and soil microbial Carbon were measured in 0, 40, and 80 days after treatment (dat), while soil respiration were observed every week. The results showed that the application of biogeotextiles and probiotics had no significant effect on soil pH, soil organic C, and soil N-Total. Microbial biomass remained stable until 80 dat, however, it tended to increase in the final growth phase, irrespective to the effect of biogeotextile and probiotic applications. Soil respiration showed a fluctuating pattern, with a significant increase on 35 and 42 day after planting. This study emphasizes the need for long-term observations to further understand the impact of biogeotextile and probiotic applications on soil biochemical properties in Andisols.